A cluster analysis of identifying team and individual sports athlete based on anthropometric, health and skill related components - Noor Aishah, Kamarudin; Mohamad Razali, Abdullah; Eswaramoorthi, Vijayamurugan; Ahmad Bisyri Husin Musawi, Maliki; Aina Munirah, Ab Rasid; Abdul Majeed, Anwar P. P.; Mohd Azraai, Mohd Razman; Musa, Rabiu Muazu (Springer Science and Business Media Deutschland GmbH, 2022)
The purpose of this study is to identify the essential fitness attributes in an individual sport and team sport. A total number of 218 male competitive youth athletes aged 13 to 21 years old were examined anthropometric, health and skill-related performance parameters (PP). Anthropometric parameters namely, weight, height, sitting height, and arm span were tested while the health-related parameters consisting of sit and reach, 1 min sit up, push up, handgrip, predicted VO2max, and medicine ball throw were also collected. The 20 m speed, vertical jump, standing wide jump, stork stand test, and t-test represented the skill-related component tests. Based on the three components, hierarchical agglomerative cluster analysis (HACA) was utilized to group the athlete concerning their similarities in the PP examined. The athletes’ performance within the clusters differs in three areas: age and arm span are significant in individual sports while height, weight, and sitting height are vital for team sports. Muscle endurance is shown to be essential in individual sports. Meanwhile, vertical jump and 20 m speed are more attributed to individual sports while standing broad jump, stork stand test, and t-test are more inclined to team sports. Some fundamental traits could determine the type of sport suitable for athletes. These traits should be prioritized for identifying team or individual sports athletes. The findings could aid coaches in making decisions about the types of sports that could best suit an athlete for better performance delivery.